Penetapan Kadar Formalin Pada Tahu Di Pasar X Dengan Metode Spektrofotometri Visible - Nanik Fitrianingsih; Choiril Hana Mustofa; Sunyoto (CERATA Jurnal Ilmu Farmasi, 2019)
Tofu is a food product in the form of soft solids made through soy processing. Formalin is a clear liquid that is colorless or almost colorless with a pungent odor, its vapors stimulate the mucous membranes of the nose and throat, formalin is a dangerous, poisonous and carcinogenic substance which is usually added to food as a preservative. This research was conducted to determine the levels of formalin in white tofu sold in traditional markets X. This research was conducted with a qualitative test using Schiff reagents and quantitative tests with Visible Spectrophotometry at a wavelength of 410 nm. The results of the study qualitatively showed that the samples tested positive contained formalin with a change in color to pink. The results of Visible Spectrophotometry readings for formalin standard solutions obtained linear regression y = 0.0537x + 0.0134 with a correlation coefficient (r2) of 0.9995. The results of formaldehyde in sample A were 23.41 mg / kg, sample B 26.57 mg / kg, sample C 58.02 mg / kg, sample D 41.71 mg / kg, and sample E were 90.35 mg / kg kg